THE INDONESIAN CORAL REEF REHABILITATION AND MANAGEMENT PROGRAM: LESSONS LEARNED IN COMMUNITY-BASED REEF MANAGEMENT AT SENAYANG AND LINGGA ISLANDS, RIAU - Dirhamsyah D. (JOURNAL OF COASTAL DEVELOPMENT, 2005)
The Coral Reef Rehabilitation and Management Program (COREMAP) is a 15-year program of theGovernment of Indonesia. It has been working at several sites in Indonesia since 1998 to achievesustainable use of coral reefs through the delegation of management authority to local communities.The establishment of effective models for participatory and community-based management is the core ofthis program. The model for community-based management includes community participation,community capacity building, promotion of alternative income generation, establishment of coral reefmanagement plans, community marine sanctuaries and community reef watcher programs. This paperdescribes the experiences and lessons learned in Phase I of the COREMAP Project in implementingcommunity-based reef management at Senayang and Lingga Islands, Riau Province. It is argued thatthe involvement of the community in the planning and implementation process of coral reef managementwill improve the management and conservation of coral reef ecosystems. It is hoped that the Indonesianexperience will contribute to the comparative literature on coral reef management.